Innate immune recognition of Neisseria meningitidis at the nasopharynx‎ - Albiheyri, Raed (2016)
Neisseria meningitidis is considered as the main suspect ‎behind the majority of meningitis and ‎sepsis cases globally. ‎The major component of the outer membrane in Neisseria, ‎‎lipooligosaccharide (LOS), is recognized by Toll-like receptor 4 ‎‎(TLR4), triggering a pro-inflammatory ‎cytokine response. ‎Particularly, TLR4 recognizes the lipid A moiety of the LOS ‎molecule, and the ‎recognition is determined by the chemical ‎composition of lipid A. The meningococcal lipid A ‎normally has ‎six acyl chains, the optimal number of acyl chains for TLR4 ‎activation. Acyl chain ‎addition is regulated by the products of ‎two genes (lpxL1 and lpxL2), which are present in a ‎number ‎of Gram-negative bacteria as well as N. meningitidis. Unlike ‎the pathogenic B serogroup, ‎the Y serogroup clonal complex ‎‎23 is pathogenic, in spite of being naturally LpxL1-deficient. ‎We ‎aimed to investigate how the changes in LOS structure ‎could affect the recognition of Neisseria ‎serogroups by the ‎host, therefore, both B and Y serogroups variants have been ‎used to infect human ‎differentiated bronchial epithelial cells ‎‎(Calu-3), cultured in an air-liquid interface. In addition, ‎mutant ‎serogroup B strains lacking lpxL1 have been ‎generated, as well as a complemented mutant strains ‎‎expressing LpxL1. LOS analysis by silver staining suggested ‎the presence of changes in the LOS of ‎the lpxL1 mutant ‎strains that could not be rescued by the complemented lpxL1 ‎gene. In addition, ‎the expression status of selected Neisseria ‎phase variant genes during the infection has been ‎‎investigated but no changes were observed. Therefore the ‎work was redirected to study bacterial ‎behaviour during the ‎infection of Calu-3. Cells analysis included bacterial growth, ‎bacterial adhesion and ‎invasion, damage to the epithelial ‎barrier and TNF-α production. Differentiated Calu-3 cells were ‎‎infected with N222.1 (Y serogroup, cc23) and two isolates, ‎designated N459.3 and N459.6. These ‎isolates were obtained ‎as two colony picks from a single nasopharyngeal swab taken ‎from the ‎same individual as isolate N222.1 but six months ‎later, and have identical strain designations (i.e. ‎ST, PorA and ‎FetA types) to N222.1. Furthermore, allelic variation was ‎detected in only five genes ‎for a whole genome comparison ‎of N459.1 to N222.1. Both N222.1 and N459.6 increased the ‎‎permeability of the epithelial barrier at 12 h post-infection and ‎induced production of high levels of ‎the pro-inflammatory ‎cytokine TNF-α. In contrast, N459.3 did not affect the ‎permeability of the ‎epithelial cell layer or induce TNF-α ‎production. Expression of Opa proteins, a family of Neisserial ‎‎adhesins that interact with CEACAMs in host cells, varies ‎among isolates and could contribute to ‎differences in their ‎phenotype. These observations contrast with those obtained ‎with control ‎serogroup B strains (MC58 and H44/76; cc32) ‎and another MenY isolate, N59.1 (cc174). The latter ‎isolate, in ‎contrast to N222.1, readily adhered/invaded the epithelial ‎layer, did not disrupt the ‎epithelial barrier, but promoted TNF-‎α production. Further work demonstrated that blocking of ‎‎TNF-α production during N222.1 infection does not protect the ‎epithelial layer from infection-‎induced damage. Preliminary ‎signalling studies showed that N222.1, N459.3 and N459.6 ‎trigger ‎distinct signaling pathways. ‎